No statistically significant difference in long term scarring outcomes of pediatric burns patients treated surgically vs. those treated conservatively - Mistry, Riyam; Issa, Fadi (Frontiers in Surgery, 2022)
Objectives Paediatric burns are a common presentation to a plastic surgery unit. The long-term scar outcomes in paediatric burns patients are relatively unknown as most are discharged after 6 weeks follow up. We aimed to determine whether the long-term scarring outcomes are significantly different in those who had surgical treatment with Versajet debridement and Biobrane, versus those treated conservatively with non-adherent dressings, in a cohort of paediatric burns patients. Methods The parents of all paediatric burns patients admitted to Stoke Mandeville Hospital from October 2014 to September 2017 were contacted by telephone to fill in the paediatric Brisbane Burn Scar Impact Profile (BBSIP), the only patient reported outcome measure (PROM) specifically aimed at children. The results from the questionnaires underwent statistical analysis to see if there was a significant difference in questionnaire scores between children treated surgically versus those treated conservatively. Results A total of 107 children were admitted in the timeframe, responses were received from 34 patients with 13 having been treated surgically and 21 having been treated conservatively. In all 58 questions that make up the BBSIP, there was no statistically significant difference observed in the scores of those treated surgically versus those treated conservatively. For 31 questions on the BBSIP, the lowest score indicating the best outcome was observed in all patients in both groups. Discussion Surgical management for burns is always the last resort. Our results could be interpreted to suggest clinicians need not fear the longer-term impact a scar may have when deciding whether to treat a paediatric burns patient surgically or conservatively. This study is the first to assess longer-term scar outcomes using the BBSIP. A larger data set and comparison with other burn units in the UK may help to provide more information on scar outcomes between different methods of surgical and conservative treatment. Conclusions We found no statistically significant difference in the long-term scar outcomes as assessed by the BBSIP in paediatric burn patients treated with Versajet debridement and Biobrane, versus those treated conservatively with non-adherent dressings.